PENGARUH DUKUNGAN SOSIAL KELUARGA TERHADAP PERILAKU ANAK AUTIS DI KOTA PEKANBARU - Aminatul Fitri; Zulfan Saam; Yulis Hamidy (Program Pascasarjana Universitas Riau, 2016)
The objectives of this research are to analyze the effect of family social support and physical environment to the behaviors of children with autism at Pekanbaru. This research is analytic-observational study with a cross-sectional and direct observation. with autism who made the same observation and stimulus 3 times for each sample observation taken using purposive sampling technique. This research showed a significant effect between emotional social support, award winning support, instrumental support, informative support, voice suddenly and unexpectedly, continuous noise and hard, light, on the behavior of children with autism at Pekanbaru in 2013. With multiple logistic regression test showed that the most dominant variables on the behavior of autistic children in Pekanbaru is a family social support P value = 0.017 and OR = 19.248.